Vulnerability and adaptation of protected areas to climate chan¬ges: case study of National Natural Parks in Ukraine - М. М. Радомська; В. В. Гузь; І. В. Ярохмедова (Науковий вісник НЛТУ України, 2022)
The observed trends of climate changes are strong enough to affect the living process in natural communities. This paper deals with the assessment of vulnerability and progress of National Natural Parks of Ukraine towards adaptation of their ecosystems to growing pressure of climate change. The vulnerability of the National Natural Parks to the effects of climate changes depends on their sensitivity, formed due to intrinsic attributes, like level of endemism and specific microclimate conditions at certain area. From the other side, some managerial solutions framed into the action plan for assisted climate adaptation of protected areas is also the factor of vulnerability or resilience. The assessment undertaken in the given paper addresses both components. At the first stage, the signs of climate changes at 51 parks of Ukraine (excluding those created less than 3 years ago) were studied based on the data from open sources, reports to the authorities and personal feedbacks from the staff. Then these data were summarized in terms of natural zones and generalized to define the most profound effects observed. Finally, the information about the presence and implementation of adaptation measures in the National Natural Parks was collected and evaluated as contributor to building adaptation capacity of the sites. Sensitivity and adaptation potential were rated using standard scale and the level of vulnerability was assigned to each park. The results showed varied level of vulnerability with the natural parks of the Steppe and Ukrainian Carpathians region demonstrating the highest levels. The research has also revealed generally low level of attention to the issues of climate changes on the whole and adaptation strategies implementation in particular in the activity of the National Natural Parks. However, some of the objects have already entered succession processes and diversity transformations. The most well studied issue is invasions, which are also the most covered by the countermeasures. Considering the uniqueness and high value of the ecosystems of the National Natural Parks of Ukraine, it is necessary to develop and implement action plans for the adaptation of these protected areas. At the same time, the problems typical for different natural parks are often specific due to attribution to certain natural zones, composition of communities, physical features of the territory and other properties, and therefore the creation of a universal adaptation procedure is complicated. Nevertheless, the article sets the main directions of work, which can become the basis of the corresponding adaptation plans of all parks.